A New Gold Rush: A Review of Current and Developing Diagnostic Tools for Urinary Tract Infections - Raymond Xu; Nicholas Deebel; Randy Casals; Rahul Dutta; Majid Mirzazadeh (Diagnostics, 2021)
Urinary tract infections (UTIs) are one of the most common infections in the United States and consequently are responsible for significant healthcare expenditure. The standard urine culture is the current gold standard for diagnosing urinary tract infections, however there are limitations of the test that directly contribute to increased healthcare costs. As a result, new and innovative techniques have been developed to address the inefficiencies of the current standard—it remains to be seen whether these tests should be performed adjunctly to, or perhaps even replace the urine culture. This review aims to analyze the advantages and disadvantages of the newer and emerging diagnostic techniques such as PCR, expanded quantitative urine culture (EQUC), and next generation sequencing (NGS).